SISTEM PEMBELAJARAN TAHFIDZUL QUR’AN DI MADRASAH TSANAWIYAH NEGERI SAMARINDA - M Isro' Zainuddin; Iskandar; Nurul Syobah (STKIP Subang, 2026)
Introduction: Tahfidzul Qur’an learning in Islamic secondary schools requires a systematic and structured learning system to ensure effective memorization outcomes. Madrasah Tsanawiyah Negeri Samarinda has implemented different tahfidz learning models across two campuses. Methods: This study employed a qualitative descriptive approach. Data were collected through non-participant observation, in-depth interviews with the headmaster, tahfidz coordinators, teachers, and students, as well as documentation analysis. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Results: The findings revealed that the tahfidzul Qur’an learning system consists of learning objectives, input, learning processes, methods, evaluation, and learning outcomes. Campus 1 applies the tasmi’ method with limited instructional time and moderate memorization targets, while Campus 2 implements both tahsin and tasmi’ methods intensively with higher memorization targets. Supporting factors include competent tahfidz teachers, adequate facilities, parental support, and strong leadership. Meanwhile, the inhibiting factors include limited learning time, differences in students’ memorization abilities, insufficient number of tahfidz teachers, and student fatigue. Discussion: The study indicates that a more intensive schedule, combined with varied methods and strong institutional support, contributes to better tahfidz learning outcomes. Therefore, strengthening management, facilities, and instructional innovation is essential to improve learning effectiveness.